2023
DOI: 10.1007/s12672-023-00675-6
|View full text |Cite
|
Sign up to set email alerts
|

ELFN1-AS1 promotes GDF15-mediated immune escape of colorectal cancer from NK cells by facilitating GCN5 and SND1 association

Abstract: The ability of colorectal cancer (CRC) cells to escape from natural killer (NK) cell immune surveillance leads to anti-tumor treatment failure. The long non-coding RNA (lncRNA) ELFN1-AS1 is aberrantly expressed in multiple tumors suggesting a role as an oncogene in cancer development. However, whether ELFN1-AS1 regulates immune surveillance in CRC is unclear. Here, we determined that ELFN1-AS1 enhanced the ability of CRC cells to escape from NK cell surveillance in vitro and in vivo. In addition, we confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…As a result, the suppression of proliferation and migration in vitro was observed. Also, Bin Han et al [ 35 ] showed that ELFN1-AS1 is upregulated in CRC tissues, correlating with poor patient survival. ELFN1-AS1 plays a significant role in CRC by promoting immune escape from natural killer (NK) cell surveillance, by enhancing CRC cells' ability to evade NK cell surveillance both in vitro and in vivo.…”
Section: Elfn1-as1 Deregulation In Cancermentioning
confidence: 99%
“…As a result, the suppression of proliferation and migration in vitro was observed. Also, Bin Han et al [ 35 ] showed that ELFN1-AS1 is upregulated in CRC tissues, correlating with poor patient survival. ELFN1-AS1 plays a significant role in CRC by promoting immune escape from natural killer (NK) cell surveillance, by enhancing CRC cells' ability to evade NK cell surveillance both in vitro and in vivo.…”
Section: Elfn1-as1 Deregulation In Cancermentioning
confidence: 99%
“… 78 GDF15 helps colon cancer cells evade NK cell surveillance by regulating their activity, in which GDF15 expression is regulated by acetylation. 79 In HBV-induced HCC, NK cells have a dual role: they are hepatoprotective and antifibrotic, but their activation can also cause liver damage. 80 NK cell-derived IFN-γ promotes HCC development through the EpCAM-EMT axis in HBV.…”
Section: Immunoregulatory Effect Of Gdf15 In Hccmentioning
confidence: 99%